2022
DOI: 10.1007/s11356-022-21556-5
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of chlortetracycline hydrochloride by peroxymonosulfate activation on natural manganese sand through response surface methodology

Abstract: This study studies the degradation of chlortetracycline hydrochloride CTC by activated peroxymonosulfate (PMS) with natural manganese sand NMS . Meanwhile, the NMS was characterized and analyzed by isothermal nitrogen adsorption (BET), X-ray energy spectroscopy (EDS) and scanning electron microscope (SEM). It can be induced that NMS material may contain C, O, Al, Si, Fe, Mn, K, and the proportion of each is 6%, 9%, 13%, 34%, 27%, 5%, 6%. Critical parameters, including initial pH value, catalyst dosage and PMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…As illustrated in Figure S10, the CTC peak disappeared in HR-MS, indicating that CTC molecules were fully degraded into small intermediates over the Co-NCNRs/CaSO 3 system. As shown in Figure S11, nine sorts of degradation intermediates in CTC degradation by Co-NCNRs/CaSO 3 were determined by the Mass library. , Based on control experiments, DFT calculation, various characterization analyses, and previously reported literature, , the mechanism of CTC degradation via the Co-NCNRs/CaSO 3 system is provided in Figure . First, SO 3 2– and CTC were adsorbed at the Co-NCNR surface.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Figure S10, the CTC peak disappeared in HR-MS, indicating that CTC molecules were fully degraded into small intermediates over the Co-NCNRs/CaSO 3 system. As shown in Figure S11, nine sorts of degradation intermediates in CTC degradation by Co-NCNRs/CaSO 3 were determined by the Mass library. , Based on control experiments, DFT calculation, various characterization analyses, and previously reported literature, , the mechanism of CTC degradation via the Co-NCNRs/CaSO 3 system is provided in Figure . First, SO 3 2– and CTC were adsorbed at the Co-NCNR surface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As shown in Figure S11, nine sorts of degradation intermediates in CTC degradation by Co-NCNRs/CaSO 3 were determined by the Mass library. 84,85 Based on control experiments, DFT calculation, various characterization analyses, and previously reported literature, 69,70 the mechanism of CTC degradation via the Co-NCNRs/CaSO 3 system is provided in •− by a series of free-radical chain reactions. Finally, CTC molecules were degraded, via the attack of various ROS, into small intermediates, CO 2 and H 2 O.…”
Section: Mechanism Insightmentioning
confidence: 99%
“…The increase in PMS concentration up to 5 mM showed an increase in COD removal due to the higher generation of SO •− 4 radicals. As the PMS concentration increased to 10 mM, results showed a reduction in COD removal (Figure 4b) due to the excess of PMS in the solution, which competed with the organic matter for the SO •− 4 radicals (Equation ( 11)) [51]. These results are in agreement with the work of Govindan et al [52], who observed that high concentrations of PMS led to the consumption of SO •− 4 radicals, decreasing the degradation of the contaminant pentachlorophenol.…”
Section: Sr-aop Optimization Through Response Surface Methodologymentioning
confidence: 99%